Respuesta :

Answer: Yes

Step-by-Step Explanation:
Ver imagen Sidharth999

Answer:

(x - 1) is a factor of 2x² - 3x + 1

Step-by-step explanation:

Method 1

If (x - 1) is a factor of f(x) = 2x² - 3x + 1  then f(1) = 0

Substitute x = 1 into the equations:

f(1) = 2(1)² - 3(1) + 1

     = 2 - 3 + 1

     = 0

Therefore, (x - 1) is a factor of 2x² - 3x + 1

Method 2

Factor  2x² - 3x + 1

Find 2 two numbers that multiply to 2 and sum to -3:  -2 and -1

Rewrite the coefficient of the middle term as the sum of these 2 numbers:

⇒ 2x² - 2x - x + 1

Factorize the first two terms and the last two terms separately:

⇒ 2x(x - 1) - 1(x - 1)

Factor out the common term (x - 1):

⇒ (2x - 1)(x - 1)

Thus proving that (x - 1) is a product of 2x² - 3x + 1